Long-term prognostic implications of type 2 diabetes mellitusin colorectal cancer patients - Alcaide, Julia; Boughanem Lakhal, Hatim; García Aranda, Marilina; Rivas-Ruiz, Francisco; Aguirre, Urko; Martin-García, Desirée; Padilla- Ruiz, María; Varela-Moreno, Esperanza; Robles-Lasarte, Marta; Baré, Marisa; Del Cura, Isabel; Morales-Suárez-Varela, María Manuela; et al. (Wiley, 2025)
Aim: Colorectal cancer (CRC) is one of the most prevalent cancers worldwide.Epidemiological evidence has identified Type 2 Diabetes Mellitus (T2DM) as a risk factorfor CRC. This study aimed to evaluate the impact of T2DM, along with clinicopathologicaland socio-demographic factors, on long-term overall survival in a large, nationally repre-sentative cohort of CRC patients with T2DM.Method: A prospective cohort of 1186 CRC patients was analysed, approximately 20% ofwhom had a diagnosis of T2DM. Kaplan–Meier estimates and multivariable Cox propor-tional hazards models were used to assess overall survival.Results: CRC patients with T2DM were more often older, had lower educational attain-ment, were former smokers, and presented higher comorbidity, right-sided tumours, priorsymptoms, depressive symptoms, elevated Body Mass Index (BMI) and lower baselinequality of life (EORTC QLQ-C30 < 75). In multivariable analysis, the co-occurrence of T2DMand depression (p = 0.007; HR 1.77; 95% CI: 1.17–2.68) and low quality of life (p = 0.04; HR1.42; 95% CI: 1.02–1.97) emerged as independent predictors of poorer long-term survival.Conclusion: Our findings highlight the compounded negative impact of T2DM and depres-sion on overall survival in CRC patients. Their combined presence significantly worsensprognosis, underscoring the need for integrated care approaches that address both physi-cal and mental health. Future research should explore targeted interventions for these co-morbidities to improve long-term outcomes and quality of life in this high-risk population.
Keywords: Cáncer colorrectal; Depresión mental; Diabetes; Cáncer -- Factores de riesgo; colorectal cancer; depression; diabetes mellitus; risk factor; survival